ANALISIS PRODUKTIVITAS, PENDAPATAN DAN KESEJAHTERAAN PETANI KARET EKS UPP TCSDP DI DESA BALAM MERAH KECAMATAN BUNUT KABUPATEN PELALAWAN - Lina Mariyati; Syaiful Hadi; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze the productivity, revenue, households income structure, to analyze the pattern of households expenditure, and to the welfare of households of the smallholder rubber plantation of ex-TCSDP development. Research was done by survey at Balam Merah Village. Data were collected from 30 small-holders rubber farmers using purposive sampling. Analysis of the results showed that the productivity of smallholder rubber plantation as 84,35 ton/ha/year, the revenues of smallholder rubber plantation as Rp. 16.738.070/ha/year. The structure of household income derived from agriculture is 91,94 percent and 8,06 percent for non-agricultural income. The pattern of household expenditure shown that the food expenditure as 27,44percent and non-food expenditures as 72,56 percent. Result also show the household of small-holders rubber plantation at Balam Merah village have the total expenditure above the poverty line (Rp. 429.452/capita/month). The household welfare using the 14 indicators of relative poverty by Indonesian Statistic show that 100 percent household have ability to fullfill the basic need or prosperous. Key words : Smallholder rubber farmer, Productivity, Income, Welfare